MENEMU-KENALI FAKTOR PENYEBAB KESALAHAN PENULISAN BAHASA ARAB DALAM TUGAS AKHIR MAHASISWA - Agussalim, Andi; Sanusi Baso, Yusring; Risky, Achmad; Widiyawati Nasir, Nur Putri; Jilan Dzakirah, Dzakiah; Vieriawan, Andi (Universitas Hasanuddin, 2023)
This study aims to identify the factors that cause Arabic writing errors in students' scientific work. This method was chosen to obtain deeper data regarding the factors causing Arabic writing errors in student scientific work. The expected solutions to the problems found are: (1) implementing vocabulary memorization every day for students; (2) using expert services to improve translations from translation machines; (3) holding training on writing Arabic scientific papers; (4) In each semester, there are nahwu and sarf courses; (5) there is a guide for the format for writing Arabic thesis; (6) before translating using a translation machine, it is better if the Indonesian grammar is arranged as well as possible; (7) there is an introduction to Arabic learning applications; and (8) using the Indonesian language full Arabic in nahwu and sarf learning.